Calculation of secondary radiation absorbed doses due to the proton therapy on breast cancer using MCNPX code. (June 2021) - Azadegan, Niloofar; Hassanpour, Mehdi; Khandaker, Mayeen Uddin; Iqbal Faruque, Mohammad Rashed; Al-mugren, K.S.; Bradley, D.A.
Abstract: Secondary radiation damage caused by proton radiation therapy can affect other tissues and result in unwanted doses. Therefore, it is necessary to calculate the secondary radiation doses (from scattering processes) for radiation protection issues. In this study, we simulated a proton beam in a 10 cm distance (from source-to-surface distance) was used to irradiate a hypothetical breast tumor at the MIRD phantom under conditions of variable beam radius and energy. Thereafter, absorbed doses to the tumor and scattering radiation doses to the heart, lung, liver, stomach, and spleen were calculated. The results showed that the maximum scattered neutron dose-to-organs close to the breast, such as the heart, lung, liver, stomach and spleen, with 70 MeV proton energy and beam radius of 1 cm are negligible. Finally, the spread-out Bragg peak was obtained using an appropriate weighted combination of beams of different energies which can be replaced as a suitable method instead of modulator wheel design for applying in MCNPX code input program. The evaluated indices in this study are the absorbed tumor doses for single particle and the scattered doses due neutrons and photons. The results showed that the majority of scattered radiation is neutrons. Scattered particle spectral powers for neutrons and photons were also plotted. It was observed that in the photon spectra, the maximum scattered radiation occurs with the beam of 1 cm radius and 70 MeV energy, while the neutron spectra show that scattered radiation is predominantly at low energy. Finally, a spread-out Bragg peak appropriate for a hypothetical tumor with 1.77 cm width was obtained, and the absorbed doses and scattered doses were calculated. Highlights: Secondary radiation from proton radiation therapy may result in unwanted doses to normal tissues. Scattering radiation doses on the heart, lung, liver, stomach, and spleen were calculated by MCNPX. The spread-out Bragg peak was obtained using the energy change method. The maximum photon scattering dose occurs in the beam with 1 cm radius and 70 MeV energy, The neutrons spectra in low energy shows the highest scattered radiation dose.